Comparative Adsorption of Different Dyes from Aqueous Solutions onto Polymer Prepared by ROP: Kinetic, Equilibrium and Thermodynamic Studies - Torgut, Gulben; Demirelli, Kadir (Springer Heidelberg, 2018)
Poly(1,2-epoxy-3-phenoxy)propane was synthesized by ring-opening polymerization using as a catalyst and benzyl alcohol as an initiator. Homopolymer's epoxy type was acylated with chloroacetyl chloride firstly and then modified with the diethanol amine. The polymers were characterized by FT-IR and . Dye adsorption properties of poly(2-phenoxy ethyl [bis(2-hydroxy ethyl)amino]acetate) were investigated by using bromocresol green (BCG), alizarin yellow (AY) and methylene blue (MB). Amounts of dye holding polymers at different times were calculated and plotted as a function of time. According to the removal results, all of the dyes reach its highest efficiency at 90 min. The effect of pH on adsorption of dyes was studied in the pH range of 2-11. Kinetic models known as pseudo-first order and pseudo-second order were used to analyze the mechanism of adsorption, and the results indicated an adsorption kinetic compatible with the pseudo-second order. The Langmuir and Freundlich isotherms were utilized to explain the adsorption equilibrium, and when it was compared with each other, it was revealed that the Langmuir isotherm model was better than Freundlich isotherm. The maximum adsorption capacities of BCG, AY and MB were 52.63, 15.87 and 31.25 mg/g, respectively. Furthermore, thermodynamic properties (, , of modified polymer were investigated for the three dyes. According to the thermodynamic parameters, the adsorption of the dyes occurred spontaneously and was endothermic. The results of this study support that novel polymer, an inexpensive and effective adsorbent, could be used for dye removal from aqueous solutions.
Keywords: Ring-opening polymerization; Modification; Dye adsorption; Kinetic and thermodynamic